ARP first aid kit, 1940-1945
1945 1939-1945 "ARP first aid kit, 1940-1945" [HFR0149a], 1940-1945 ARP first aid kits were produced by Boots and other companies for ARP Wardens, Fire Watchers and for both workplace and domestic use. This box, belonging to a London firewatcher, Rosie Coates, includes gas eyeshields, face mask, ointment and various dressings.